Integrated Use of Biofertlizers with Organic and Inorganic Phosphorus Sources Improve Dry Matter Partitioning and Yield of Hybrid Maize. Issue 21 (30th November 2021) - Amanullah,; Khalid, Shah; Muhammad, Asim; Yar, Mohammad; Ahmad, Manzoor; Akram, Hafiz M.; Imran,; Al-Tawaha, Abdel Rahman M.; Ullah, Saif; Ali, Izhar; Fahad, Shah; Adnan, Muhammad; et al.
ABSTRACT: Phosphorus (P) unavailability and lack of organic matter in calcareous soils under semiarid climates are major reasons for low maize productivity grown in these conditions. The hypothesis was tested that integrated use of biofertilizers (BF) and P -sources could improve dry matter (DM) partitioning and yield of hybrid maize (CS-200) in the semiarid climate of Peshawar. A field trial was conducted to investigate the impact of two BF-sources, and eight organic and inorganic P-sources combinations (P) on DM partitioning, yield, and yield components of hybrid maize. The research was conducted at the Agronomy Research Farm of The University of Agriculture Peshawar, during summer 2017. Experiment was laid out in randomized complete block design with split plot arrangement, using four replications. Combination of inorganic-P [single super phosphate (SSP) and rock phosphate (RP)] and organic-P (compost and biochar) sources was used as factor-A, and BF [Phosphate Solubilizing Bacteria (PSB) and Trichoderma (TD)] as factor-B. Phosphorus was applied at the uniform rate of 120 kg ha −1 from different sources (08 treatments). The results revealed that P sources and BF had significantly affected all parameters under study. As compared with TD, application of PSB had significantly increased total plant dry weight (TDW), leaf dry weight (LDW), cob dry weight (CDW), husks dry weigh (HDW), stem dry weight (SDW), and roots dry weight (RDW) at both silking and physiological maturity. The highest ear length (EL), more number of grains per row (NGPR), number of rows per ear (NRPE), number of grains per ear (NGPE), heavy thousand grains weight (TGW), higher total biological yield above ground (BY), grain yield (GY), stover yield (SY), harvest index (HI), and shelling percentage (SP) were obtained with application of PSB over TD. As compared with sole biochar (T3), application of organic-P in the form of sole compost (T4) had significantly increased plant TDW (188.8 g & 312.9 g), LDW (34.3 g & 29.0 g), CDW (41.9 g & 176.1 g), HDW (25.9 g & 21.7 g), SDW (85.4 g & 65.6 g), RDW (26.9 g & 15.2 g) at silking and physiological maturity, respectively. Significantly higher yields (GY, SY, BY, HI & SP) and yield components (EL, NGPE, NRPE & TGW) were recorded with sole compost application (T4) or combined application of compost + SSP (T6). Among all possible interactions of BF and treatments (2 x 8 = 16 combinations), the integrated use of PSB x T4, and PSB x T6 was found to the most beneficial combinations for improving DM partitioning, yield and yield components of hybrid maize in the study area. Interestingly, the integrated use of BF with RP (T7 & T8) had more positive effect on DM partitioning, yield and yield components of hybrid maize than sole application of RP (T2).